A Decentralized Approach to Drone Formation Based on Leader-Follower Technique - Neto, Amador; Romero, Roseli (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
In recent years, the control of drones has been the focus of several studies, since they have been used in several applications. In this article, a layered control architecture is being proposed to decentralize the development of the control system. Different modes of follow-up with formation, based on the leader-follower strategy, are investigated. These formation algorithms were implemented and compared in the ROS environment using Gazebo simulator. Experiments performed considering some test cases demonstrate good performance and robustness of the proposed system.